UTP IMS: WEB-BASED INTERNSHIP MANAGEMENT SYSTEM - Azahar, Miza Aida Nadia (IRC, 2019)
Student Industrial Internship Program (SIIP) is a program that every student needs to undergo industrial training before being allowed to graduate from Universiti Teknologi Petronas (UTP). In average, 500 students are going into the industrial world to undergo the training for every semester with various companies in various places including the overseas. This dissertation is written for the development of UTP IMS: Web-Based Internship Management System for Universiti Teknologi Petronas (UTP). Most of the processes for the SIIP program in UTP are being executed manually. The aim of this project is to develop a web-based internship management system to automate and computerize the current manual processes by performing the internship registration, online-logbook submission, online reports submission, assignation of supervisors and monitoring the students’ progresses through the system. To complete this project, two phases of methodology are being use which are preliminary studies and system development. To conduct the preliminary studies, literature review of the project and interviews the stakeholders were executed. For system development, Waterfall methodology was implemented for the System Development Life Cycle (SDLC) technique and the project will be going through four phases which are Planning, Analysis, Design and, Development and Testing, and Deployment.